Very Metal-poor Stars in the Solar Vicinity: Kinematics and Abundance Analysis - Anastasiia Plotnikova; Giovanni Carraro; Sandro Villanova; Sergio Ortolani (The Astrophysical Journal, 2023)
Very metal-poor stars contain crucial information on the Milky Way’s infancy. In our previous study we derived a mean age of ∼13.7 Gyr for a sample of these stars in the Sun’s vicinity. In this work, we investigate the chemical and kinematic properties of these stars with the goal of obtaining some insights into their origin and their parent population. We did not find any Al–Mg anticorrelation, which leads us to the conclusion that these stars did not form in globular clusters, while the detailed analysis of their orbital parameters reveals that these stars are most probably associated with the pristine bulge of the Milky Way. We then sketch a scenario for the formation of the Milky Way in which the first structure to form was the bulge through rapid collapse. The other components have grown later on, with a significant contribution of accreted structures.